Comparative effect of in-person and virtual methods of eye movement desensitization and reprocessing on the fear of COVID-19 among nurses: a three-armed randomized control trial - Mohammadreza Sheikhi; Seyyed Mehdi Mousavi; Mohammad Moradi Baglooei; Mark D. Griffiths; Zainab Alimoradi (Cogent Psychology)
During the COVID-19 pandemic, the fear of COVID-19 increased, especially among nurses. The present study investigated the effect of in-person and virtual methods of Eye Movement Desensitization and Reprocessing (EMDR) on the fear of COVID-19 among nurses. In a three-armed randomized control trial, the sample comprised 141 nurses working in hospitals affiliated to Qazvin University of Medical Sciences, Qazvin, Iran. Eligible individuals were randomly assigned in study groups (virtual EMDR, in-person EMDR, and control) using balanced block method with a block size of six. The main outcome of the study was the fear of COVID-19 assessed before, immediately after, and three months after intervention. The secondary outcomes assessed included anxiety, depression and work-related quality of life assessed before and three months after the intervention. The results of variance-covariance analysis for repeated measures showed a significant reduction in the mean score fear of COVID-19 immediately after and three months after the intervention in the in-person EMDR intervention group compared to the virtual group (mean difference equal to -3.48 and -3.57) and the control group (mean difference equal to -5.45 and -5.57). Considering the minimum clinically significant difference was equal to 2.54 on the Fear of COVID-19 Scale, this reduction was also clinically significant. The average number of intervention sessions was two. No significant difference was observed regarding anxiety, depression and work-related quality of life after intervention between all three groups. In-person EMDR is more effective than the virtual EMDR as a non-pharmacological method in the treatment of fear of COVID-19 among nurses. In-person EMDR should be conducted in preference to virtual EMDR. However, in situations where in-person EMDR cannot be conducted, virtual EMDR could be considered as a potential alternative.